Coercive, Mimetic, and Normative Isomorphism Studies on the Implementation of Teacher Certification Policies in Indonesia - Fany, Yulia Gita (International Journal of Social Science and Business, 2022)
This study aims to analyze teacher certification policies using the theory of institutional isomorphism, popularized by DiMaggio and Powel (1983) as a theory of organizational sociology, where this theory explains the mechanisms of change that occur within an institution/entity to lead to homogeneous conditions. The teacher certification policy is one of the priority programs of the Ministry of Education, Culture, Research, and Technology (MOECRT) where this program is implemented in the context of producing professional teachers who are expected through professional teachers to realize quality national education. This research is a qualitative descriptive study by utilizing literature studies related to institutional isomorphism and teacher certification as well as institutional narratives in the form of government regulations, ministry regulations, technical guidelines, and also implementation guidelines for implementing the teacher certification program since its inception, which is in 2006. From the results of the analysis of the literature study, a study of various rules and implementation guidelines as well as the results of the author's observations, it is found that the implementation of the teacher certification program has undergone several policy changes that have resulted in changes in the pattern of teacher certification in LPTKs/universities. From the point of view of isomorphism, interventions that ultimately lead to changes in policies and patterns of teacher certification can be identified as coercive pressures stemming from structural regulation, normative pressures stemming from professional interventions such as involvement of academics in policymaking, as well as mimesis driven by the desire to be like other entities that are considered successful which in this case reflects on the implementation of medical professional certification.